Pengawasan Partisipatif Masyarakat Dalam Pemilihan Umum Serentak Presiden/Wakil Presiden Dan Pemilihan Umum Legislatif Tahun 2019 Di Kabupaten Kapuas - Tity Yukrisna; M. Riban Satia; R. Biroum Bernadianto (Pencerah Publik, 2020)
The purpose of this research is to see the supervision of elections conducted to realize the election held democratically, direct, common, used, confidential, honest, fair and quality. The success of electoral implementation is a common necessity for all people. Because only thus elected quality figures to lead the nation. The supervision of election implementation is a shared responsibility. People can conduct supervision with participatory supervision. The method of research is qualitative, data collected using methods of interview techniques, observations, and documents. Data processing is done with qualitative, which is using an interactive data analysis model. The results of the study showed: (1) The practice of participatory supervision was carried out by forming a "participatory supervision village" which was held in Basarang subdistrict namely Basarang Jaya Village, Straits district of Inner Straits and Kecamatan Kapuas Hulu in Desa Dirung Koram; (2) Supervision pattern developed namely coaching, socialization, discussion, and deliberation with the community leaders level RT, RW, the Arisan of the chairman of the RT every Saturday night, fitness gymnastics by mothers. and others; (3) Community participatory supervision village has contributed quite significantly to the results of the election implementation in the region, almost all villages/villages that become participatory supervision village successfully carried out the electoral activities safely, orderly, smoothly without any fraud measured by 0% report violations; Research advice is (1) need to increase participatory election supervisory training activities in community groups at village/Kelurahan in all areas of the subdistrict; (2) Provide more socialization to the community layer; (3) Develop the presence of participatory supervision village that has been to become political culture, and form a participatory supervision village in all villages and sub-districts in Kapuas and central Kalimantan